Secretoneurin and neurogenic inflammation. - Wiedermann Christian J; Dunzendorfer Stefan; Kahler Christian M; Reinsch Norbert; Schratzberger Peter (Acta Pharmacologica Sinica; Vol 20, No 9 (September 1999): Acta Pharmacologica Sinica, 2016)
Secretoneurin and neurogenic inflammation. Christian J WIEDERMANN%Stefan DUNZENDORFER%Christian M KAHLER%Norbert REINSCH%Peter SCHRATZBERGER "AIM: Review of evidence that the 33-amino-acid polypeptide secretoneurin, which is generated by proteolytic cleavage of secretogranin II, plays a role in neurogenic inflammation. METHODS: Survey of the literature using a MEDLINE search database. RESULTS: Secretoneurin is synthesized in spinal ganglia, transported through the dorsal roots and stored in the axon terminals of primary afferent neurons. Investigations using capsaicin suggest that secretoneurin functions as an excitatory transmitter. Secretoneurin specifically activates various cell functions including the chemotactic migration of monocytes, eosinophils, fibroblasts, smooth muscle cells, and endothelial cells, which suggests that the peptide may modulate inflammatory reactions. Secretoneurin receptors have been functionally characterized. They are G-proteins linked and effects are abrogated by inhibition of protein kinase C. CONCLUSION: With actions as diverse as those seen with other mediators such as tachykinins, secretoneurin may be considered another sensory neuropeptide with modulatory potential in neurogenic inflammation.